The Effects of Vortex Generator Types on Heat Transfer and Flow Structure in a Rectangular Duct Flows - Mohammed, Waheed S.; Ahmed, Sabah Tarik; H., Laith J. (Al-Khwarizmi Engineering Journal, 2008)
In this numerical study a detailed evaluation of the heat transfer characteristics and flow structure in a laminar and turbulent flow through a rectangular channel containing built-in of different type vortex generator has been a accomplished in a range of Reynolds number between 500 and 100,000.A modified version of ESCEAT code has been used to solve Navier-Stokes and energy equations. The purpose of this paper is to present numerical comparisons in terms of temperature, Nusselt number and flow patterns on several configurations of longitudinal vortex generator including new five cases. The structures of heat and flow were studied, using iso-contours of velocity components, vortices, temperature and Nusselt number. This study shows that the predicted structures of fluid flow, temperature fields and Nusselt number variation are strongly affected by the presence of the turbulators. Staggered arrangement gains high Nusselt number, also the lower and upper arrangements have higher Nusselt number than plane duct. High Reynolds number (higher air inlet velocity) will enhance the Nusselt number. Increase in ribs height will enhance the heat transfer as it works as surface area and turbulator at the same time.